A Translation from Object-Based Hypergraph Grammars into π-Calculus - Foss, Luciana; Ribeiro, Leila (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2004)
Object-based models offer abstract constructions to describe complex systems. The Object-Based Graph Grammar (OBGG) is a very intuitive formalism that may be used to describe this kind of systems. To be really useful in practice, there should be a (preferably automatic) way to verify whether the desired properties of a system are fulfilled by the model constructed using graph grammars. However, up to now, there are no automatic tools for verification of OBGGs. In this work we propose a translation from Object-Based Graph Grammars into π-Calculus. So, we may be able to prove properties of systems modeled in OBGGs using existing automatic checkers for π-calculus.